The effect of COVID-19 on the hospitality industry: The implication for open innovation - Kanwal Iqbal Khan; Amna Niazi; Adeel Nasir; Mujahid Hussain; Maryam Iqbal Khan (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The current coronavirus pandemic (COVID-19) has led the world toward severe socio-economic crisis and psychological distress. It has severely hit the economy; but the service sector, particularly the hospitality industry, is hard hit by it. It increases the sense of insecurity among the employees and their perception of being unemployed, adversely affecting their mental health. This research aims to contribute to the emerging debate by investigating the effect of economic crisis and non-employability on employees' mental health through perceived job insecurity under the pandemic situation. It empirically examines the underlying framework by surveying 372 employees of the hospitality industry during COVID-19. Results indicate that perceived job insecurity mediates the relationship of fear of economic crisis, non-employability, and mental health. Furthermore, the contingency of fear of COVID-19 strengthens the indirect relationship of fear of economic crisis on mental health through perceived job insecurity. The findings will provide a new dimension to the managers to deal with the psychological factors associated with the employees' mental health and add to the emerging literature of behavioral sciences. The study also highlights the increasing need for investment in the digital infrastructure and smart technologies for the hospitality industry.
Keywords: 650; COVID-19; digital infrastructure; fear of COVID-19; fear of economic crisis; hospitality industry; mental health; non-employability; perceived job insecurity